Etika Komunikasi Islam dalam Praktik Digital UMKM Melalui Whatsapp (Studi pada Nasi Kuning Tante Jum) - Zarah Indriyani; Rasni .; Ahmad Sultra Rustan; Sumarni Sumai (JKOMDIS : Jurnal Ilmu Komunikasi Dan Media Sosial, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the economy and are required to adapt to technological developments in the digital era, including the use of WhatsApp as a communication and marketing medium. WhatsApp is considered effective because it facilitates fast, practical, and direct interaction between business owners and customers. In addition, its use is closely related to the implementation of Islamic communication ethics, which emphasize the values of honesty, trustworthiness, and politeness. This study aims to examine digital communication practices through WhatsApp at Nasi Kuning Tante Jum MSME and to analyze the implementation of Islamic communication ethics in its digital communication activities. This study employs a qualitative approach with a descriptive research design. The research was conducted at the Nasi Kuning Tante Jum MSME in Pinrang Regency, utilizing purposive sampling to select informants, who comprised the business owner, the owner's child, and customers. Data were gathered through observation, in-depth interviews, and documentation. The collected data were then analyzed using the Miles and Huberman model, which encompasses data reduction, data display, and conclusion drawing/verification. To ensure data trustworthiness, validity was tested through method triangulation. The findings reveal that WhatsApp is used as the primary medium for receiving orders, promoting products, and communicating with customers at Nasi Kuning Tante Jum MSME. The use of WhatsApp is considered effective in facilitating interactions between sellers and consumers. Furthermore, the digital communication practices implemented by the business reflect the principles of Islamic communication ethics, including honesty (ṣidq), trustworthiness (amanah), effective message delivery (tabligh), brotherhood (ukhuwah), and politeness in communication. These values are reflected in friendly, honest, and responsive customer service, which helps build customer trust and loyalty. Although internet connectivity remains a challenge, the quality of service is consistently maintained.